2011
DOI: 10.1097/ta.0b013e3181dbe5f7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Foot and Ankle Kinematics After Operative Reduction of High-Grade Intra-Articular Fractures of the Calcaneus

Abstract: In high-grade calcaneal fractures, when recreation of gross calcaneal anatomy is obtained during the operation, walking ankle motion is recreated as well. However, subtalar motions, although recreated to a certain extent, still demonstrate limitations when compared with noninjured individuals. These results support the advisability of the operation in these complex injuries, but they demonstrate that subtalar motion is not completely normalized despite a favorable anatomic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…This number of patients is in line with previous studies reporting on foot and ankle kinematics, using a MSFM. [ 7 , 13 , 14 , 22 , 24 – 28 ] When patients were divided by age, 13 subjects (17 feet) were included in the younger adults group and 8 subjects (14 feet) in the older adults group. These groups were smaller.…”
Section: Discussionmentioning
confidence: 99%
“…This number of patients is in line with previous studies reporting on foot and ankle kinematics, using a MSFM. [ 7 , 13 , 14 , 22 , 24 – 28 ] When patients were divided by age, 13 subjects (17 feet) were included in the younger adults group and 8 subjects (14 feet) in the older adults group. These groups were smaller.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that vertical ground reaction forces (VGRFs) and kinematics were altered in patients after calcaneal bone pathology [1][2][3][4][5][6][7]. It is unclear whether altered kinematics in patients correlate with altered VGRFs, but if so, then VGRFs can hypothetically be used as a screening instrument to identify patients with altered foot and ankle kinematics who need a more detailed kinematic analysis with a multisegment foot model (MSFM) [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Both manual and implantary compression can further recreate the width and height of the calcaneus [22,24]. When recreation of gross calcaneal anatomy is obtained during the operation, walking ankle motion is recreated as well [27]. In the current study, gross anatomical calcaneal structures were achieved in all patients, and a normal walking gait was regained for each patient at the follow ups.…”
Section: Discussionmentioning
confidence: 72%
“…For all practical purposes, ORIF remains the treatment of choice for such injuries at many orthopaedic trauma centres [27]. The majority of orthopaedic surgeons emphasise anatomical reduction of the articular surfaces of the subtalar joint, especially the posterior articular surface.…”
Section: Discussionmentioning
confidence: 99%